Kiefer e I Sette Palazzi Celesti. Ovvero l’inizio come la fine e l’inverso - Vercellone, Federico (Bollettino Filosofico, 2017)
The Seven Palaces of the Sky in the Pirelli HangarBicocca represent an artistic document of primary significance concerning the meaning of modernity. They are set in the context of a Modern Architecture and seem to be in a conflictual relationship with it. We have to do with a conflict regarding the concept of time in the late-Modernity and the way in which it is lived and conceived. The Seven Palaces of the Sky are ready to fall down while the Architecture of HangarBicocca is devoted to a rationalistic eternity. From this local conflict the text draws some considerations on the destiny of our time and of the conception of it.